What about the Misgav-Ladach Surgical Technique in Patients with Previous Cesarean Sections? - Bolze, Pierre-Adrien; Massoud, Mona; Gaucherand, Pascal; Doret, Muriel (American Journal of Perinatology, 2013)
Objective The Misgav-Ladach technique is recommended worldwide to perform cesarean sections but there is no consensus about the appropriate technique to use in patients with previous cesarean sections. This study evaluated the feasibility of the Misgav-Ladach technique in patients with previous cesarean sections.Study Design This prospective cohort study included all women undergoing cesarean section after 36 weeks of gestation over a 5-month period, with the Misgav-Ladach technique as first choice, whatever the previous number of cesarean sections.Results Among the 204 patients included, the Misgav-Ladach technique was successful in 100%, 80%, and 65.6% of patients with no, one, and multiple previous cesarean sections, respectively. When successful, the Misgav-Ladach technique was associated with a shorter incision to birth interval in patients with no previous cesarean section compared with patients with one or multiple previous cesarean sections. Anterior rectus aponeurosis fibrosis and severe peritoneal adherences were the two main reasons explaining the Misgav-Ladach technique failure.Conclusion The Misgav-Ladach technique is possible in over three-fourths of patients with previous cesarean sections with a slight increase in incision to birth interval compared with patients without previous cesarean section. Further studies comparing the Misgav-Ladach and the Pfannenstiel techniques in women with previous cesarean should be done.
Keywords: previous cesarean section; Misgav-Ladach; cesarean technique; incision to birth interval